PENGARUH PENGGUNAAN VIRTUAL LABORATORY DALAM PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM LEARNING (STL) TERHADAP HASIL BELAJAR FISIKA SISWA MAN 2 PADANG - Renold Fernanda; Ratnawulan Ratnawulan; Hidayati Hidayati (Universitas Negeri Padang, 2015)
One of the subjects that are important for the development of science and technology is the study of Physics. The results obtained by the students in learn physics is still low. Media that are less attractive and less effective learning strategies in the learning process of physics to be the cause . Physics learning process can be improved by applying learning media in the form of a virtual laboratory with cooperative learning model Student Team Learning. The type of this research is “quasi experiment research” with “Randomized Control Group Only Design” . The population of this research is students of class X MAN 2 Padang listed in the Academic Year 2013/2014 . Sample was collected by cluster random sampling . The data of the research were the student’s learning outcomes in the area of cognitive aspects, affectif aspects, and psychomotor aspects. The research’s instrument are test sheet (multiple choice) for cognitive aspects, observation sheet for affective aspect, and score rubric for phychomotor aspect. The result of this research showed that the mean score of the experimental class was higher then control class. There is the influence of the use of Virtual Laboratory in cooperative learning Student Team Learning ( STL ) to the physics student learning outcomes in MAN 2 Padang